Student learning style in vocational higher education - Auliana Nasution; Ambiyar Ambiyar; Wakhinuddin Simatupang (Universitas Negeri Padang, 2021)
When student learning styles are known, teaching can be designed according to student interests through teaching strategies, teaching methods and techniques, and selecting and applying the necessary teaching tools. This research aims to describe vocational students' learning styles using Forster learning styles and investigate the relationship between these learning styles and mathematics learning achievement. Researchers analyzed vocational students' mathematics learning styles using the